2007
DOI: 10.1007/s11104-007-9474-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter dynamics under soybean exposed to elevated [CO2]

Abstract: It is unclear how changing atmospheric composition will influence the plant-soil interactions that determine soil organic matter (SOM) levels in fertile agricultural soils. Positive effects of CO 2 fertilization on plant productivity and residue returns should increase SOM stocks unless mineralization or biomass removal rates increase in proportion to offset gains. Our objectives were to quantify changes in SOM stocks and labile fractions in prime farmland supporting a conventionally managed corn-soybean syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…Such differences may be ecosystem-dependent. A previous study showed that as soybean yield and root biomass increased under eCO 2 , soil organic matter turnover was accelerated but soil moisture and nutrients were not limiting factors at the SoyFACE (Peralta and Wander, 2008). Compared with grassland ecosystems, the soybean agro-ecosystem is N-rich and has competive advantages over non-legumious species at eCO 2 by capitializing on eCO 2 benefits (for example, increaseing N fixation) and limiting deleterious eCO 2 effects (Rogers et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such differences may be ecosystem-dependent. A previous study showed that as soybean yield and root biomass increased under eCO 2 , soil organic matter turnover was accelerated but soil moisture and nutrients were not limiting factors at the SoyFACE (Peralta and Wander, 2008). Compared with grassland ecosystems, the soybean agro-ecosystem is N-rich and has competive advantages over non-legumious species at eCO 2 by capitializing on eCO 2 benefits (for example, increaseing N fixation) and limiting deleterious eCO 2 effects (Rogers et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…and corn, Zea mays L. for more than 25 years, and the soil at the site is a Drummer fine-silty, mixed, mesic Typic Endoaquoll, typical of wet, dark-colored 'prairie soils' in northern and central Illinois (Pujol Pereira et al, 2011). More soil background properties, including soil pH, moisture, Bray P, K, Ca and Mg were previously documented (Peralta and Wander, 2008). SoyFACE aims to discover the effects of atmospheric change on the agronomy, productivity and ecology of Midwestern agro-ecosystems planted in a typical corn-soy rotation.…”
Section: Site Description and Samplingmentioning
confidence: 88%
“…In many natural and semi-natural ecosystems, the CO 2 -induced stimulation of plant growth may not persist because of nutrient limitation [9,39]. In agricultural ecosystems, however, N is typically not a limiting factor for plant growth due to the application of chemical N fertilizers and/or the incorporation of legume plants, and CO 2 -stimulation of biomass production is expected to be sustained [2,31,66]. Therefore, it has been suggested that elevated CO 2 can increase long-term C storage in agroecosystems, particularly in combination with no-tillage management [38,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased N contents can boost microbial respiration and population growth, resulting in accelerated N turnover and net mineralization from decomposition of microbial residues (Mengel 1996;Ebersberger et al 2003). The AN may also support root accelerated mineralization of SOM (Peralta and Wander 2008). Moreover, GFG-dominated meadows had lower pH values, which may impact plant rhizosphere secretion, soil acidity, and the organic acids released during the decomposition process.…”
Section: Discussionmentioning
confidence: 99%